2019
DOI: 10.1093/intqhc/mzz061
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric clinician perspectives on communicating diagnostic uncertainty

Abstract: Objective Diagnosis often evolves over time, involves uncertainty, and is vulnerable to errors. We examined pediatric clinicians’ perspectives on communicating diagnostic uncertainty to patients’ parents and how this occurs. Design We conducted semi-structured interviews, which were audiotaped, transcribed, and analyzed using content analysis. Two researchers independently coded transcripts and then discussed discrepancies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 26 publications
0
37
0
2
Order By: Relevance
“…Poor trust in clinicians may be a barrier to treatment adherence, as high parent-reported patient satisfaction and positive expectations of treatment results have been associated with better treatment adherence in pediatric chronic pain [ 29 ]. From the perspective of health care providers, one thematic analysis found that pediatric providers also experience diagnostic uncertainty, but how much they communicate their own diagnostic uncertainty likely depends on parent characteristics and the strength of the parent-provider relationship [ 30 ]. In addition, some qualitative diagnostic uncertainty responses in the present study indicated an intent to see additional providers.…”
Section: Discussionmentioning
confidence: 99%
“…Poor trust in clinicians may be a barrier to treatment adherence, as high parent-reported patient satisfaction and positive expectations of treatment results have been associated with better treatment adherence in pediatric chronic pain [ 29 ]. From the perspective of health care providers, one thematic analysis found that pediatric providers also experience diagnostic uncertainty, but how much they communicate their own diagnostic uncertainty likely depends on parent characteristics and the strength of the parent-provider relationship [ 30 ]. In addition, some qualitative diagnostic uncertainty responses in the present study indicated an intent to see additional providers.…”
Section: Discussionmentioning
confidence: 99%
“…Study designs included quantitative, 23,[36][37][38][39][40] mixed methods, 25,41,42 and qualitative. [43][44][45][46][47][48][49][50][51][52] Studies were published between 1991 and 2019 and conducted predominantly in the USA (n=10) and UK (n=4).…”
Section: Search Resultsmentioning
confidence: 99%
“…38 The predominant race (between 68% and 87%) of participants was white 36,38,42 and most had completed high school education or higher. 25,36,41,42 Of the 19 articles, less than half (n=8) included definitions for expressions of uncertainty 25,38,40,41,46 or diagnostic uncertainty 39,48,52 (frequently adopting or adapting Bhise et al's definition 53 ). Expressions of uncertainty were defined generally (e.g.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,25 Prognostic uncertainty is a common feature of care for children with neurological conditions, and clinician approaches are variable; parents appreciated when clinicians were honest about this uncertainty. 25,26 Interventions to improve communication skills have been effective in many disciplines and should be adapted to this context. [27][28][29][30][31][32][33] Most parents emphasized the need for clinicians to understand and validate their experiences.…”
Section: Discussionmentioning
confidence: 99%